Francisco Goya, 1746-1828 on the threshold of modernity - Hagen, Rose-Marie; Hagen, Rainer (Taschen, 2012)
In 1774 Francisco Goya moved to Madrid. He had been commissioned to design tapestries for the Royal Tapestry Factory of Santa Barbara. His age: 28. He had grown up in the provinces, in Saragossa, where he trained under local artists. He had secured the tapestry commission not because of his striking talent, but through family connections. He had got married the year before his brother-in-law, a well-regarded painter in Madrid, arranged the job for him.